Sharia accounting model in the perspective of financial innovation - Firman Menne; La Ode Hasiara; Adil Setiawan; Palipada Palisuri; Andi Mattingaragau Tenrigau; Waspada Waspada; Juliana Juliana; Nurhilalia Nurhilalia (Journal of Open Innovation: Technology, Market and Complexity, 2024)
Sharia accounting has undergone significant development along with the advancement of technological innovation and dynamics in the Islamic business world. The purpose of this study is to investigate and review the literature on sharia accounting and financial innovation to identify relevant sharia accounting models to be developed that can be integrated with financial innovation. This study also provides suggestions for future sharia accounting research. The method used in this research is a systematic literature review method that involves the analysis and synthesis of relevant literature. The findings of this study indicate that the development of an sharia accounting model in the perspective of financial innovation, makes sharia accounting more competitive, by offering fast and accurate preparation and presentation of financial statements, improving the operational efficiency of Islamic business entities, especially SMEs, in terms of financial reporting, compliance with sharia principles, and meeting the organization's social obligations. This research provides a positive contribution for policy makers such as regulators and investors in making policies, making regulations and preparing infrastructure that can support the development of sharia accounting models in the future. The limitation of this research is that the design is still qualitative so that it still requires more comprehensive and practical analysis, and encourages further research involving wider variables, such as the quality of human resources, Islamic financial inclusion and literacy, and the role of the government in strengthening the development of sharia accounting based on financial innovation.